L’échappée belle d’élèves étiquetés vulnérables : des bacheliers professionnels en CPGE - Carine Érard; Christine Guégnard; Magali Danner (Éducation et Socialisation)
Given the purpose of their degree, vocational secondary education graduates do not generally seem to belong to the preparatory class leading to “Grandes Écoles” (CPGE). Stigmatised by a vocational track, they appear weak, because their social and school profile does not match with the content of the long programmes of higher education. However some of them venture into these programmes for elites. On the basis of semi-direct interviews, we attempt at presenting their standpoint, as they look for meaningful higher education and try to align their school career, their experiences and their expectations. Aware of the obstacles but without seeing themselves as vulnerable, these vocational baccalauréat holders accept the risks of such an unusual orientation in higher education: the CPGE represents the hope of escaping the destiny associated with the vocational track that they have appreciated.